(untitled) (Journal of Governance and Development (JGD), 2014)
Purpose - The influence of Islamic management practices on managers’ performance such as organizational commitment involves the development of an individual’s abilities and attitudes contribute towards organizational interests. Therefore, this paper examined the effect of motivational role of budget participation among Muslim managers in Malaysian Local Authorities. In particular, this study aims to indentify the mediating effects of organizational commitment as motivational role in budget participation and managerial performance relationship. Design/ Methodology/Approach - A Structural equation modeling was utilised to examine the direct and indirect effects of motivational role of budget participation among Muslim managers through path analysis. Findings – The result indicate that the mediating effect of organizational commitment strengthened the budget participation and managerial performance relationship. Research Limitations - This research survey only conducted in local governments organization. Thus, result may not be generalized to other public organizations. Originality/Value – The findings from this study can have practical relevance in the Islamic current management setting in Malaysian government organization. The results provide insights on the role of Islamic organization commitment as management approach by Muslim managers in evaluating their performance.